The association between headache and low back pain: a systematic review - Arani Vivekanantham; Claire Edwin; Tamar Pincus; Manjit Matharu; Helen Parsons; Martin Underwood (The Journal of Headache and Pain, 2019)
Abstract Background To systematically review studies quantifying the association between primary chronic headaches and persistent low back pain (LBP). Main text We searched five electronic databases. We included case-control, cross-sectional and cohort studies that included a headache and back pain free group, reporting on any association between persistent LBP and primary headache disorders. Methodological quality was assessed using Newcastle-Ottawa Scale. Our primary outcome was the association between primary headache disorders and persistent LBP. Our secondary outcomes were any associations between severity of LBP and severity of headache, and the relationship between specific headache sub-types classified as per International Classification of Headache Disorders (ICHD) criteria and persistent LBP. We included 14 studies. The sizes of the studies ranged from 88 participants to a large international study with 404, 206 participants. Odds ratios for the association were between 1.55 (95% confidence interval (CI) 1.13–2.11) and 8.00 (95% CI 5.3–12.1). Study heterogeneity meant statistical pooling was not possible. Only two studies presented data investigating persistent LBP and chronic headache disorders in accordance with ICDH criteria. Conclusions We identified a positive association between persistent LBP and primary headache disorders. The quality of the review findings is limited by diversity of populations, study designs and uncertainly about headache and LBP definitions. Trial registration PROSPERO 2018 CRD42018086557.